2006
DOI: 10.1139/g05-119
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the retrotransposon BARE-1 reveals the dynamic nature of the barley genome

Abstract: We used quantitative real-time PCR analysis to measure the copy number of the BARE-1 retrotransposon in 5 cultivars of barley (Hordeum vulgare), as well as in samples from its wild relative, Hordeum spontaneum. Two sets of PCR primers were used to amplify regions within the long terminal repeat (LTR) and the reverse transcriptase (RT) gene of BARE-1 (GenBank accession Z17327). The LTR primers detected an average of 2.148 x 105 +/- 0.012 x 105 copies per haploid genome among barley samples, whereas the RT prime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 46 publications
3
21
0
Order By: Relevance
“…Sun et al, (2001), the discrepancy between pedigree and molecular markersbased genetic diversity estimates may be caused by selection pressure for different breeding objectives. The results also revealed that pattern of grouping did not match well with available pedigree information which is in accordance with the results reported in oats (O'Donoughue et al, 1994), bread wheat (Barrett et al, 1998;Almanza-Pinzon et al, 2003, Soleimani et al, 2002. This analysis led to detection of 107 alleles (Table 2), with a mean of 2.55 alleles per locus.…”
Section: Resultssupporting
confidence: 83%
“…Sun et al, (2001), the discrepancy between pedigree and molecular markersbased genetic diversity estimates may be caused by selection pressure for different breeding objectives. The results also revealed that pattern of grouping did not match well with available pedigree information which is in accordance with the results reported in oats (O'Donoughue et al, 1994), bread wheat (Barrett et al, 1998;Almanza-Pinzon et al, 2003, Soleimani et al, 2002. This analysis led to detection of 107 alleles (Table 2), with a mean of 2.55 alleles per locus.…”
Section: Resultssupporting
confidence: 83%
“…One member of the family, the Bd2_RLC_14 element, is 20,769 years old and has 35 related solo LTRs. This is consistent with the high turnover seen for BARE elements in the Hordeum genome (Soleimani et al 2006;Vicient et al 1999b). Although the retrotransposon population of the genome, in evolutionary terms, has been removed rapidly, they are nevertheless continuing to propagate.…”
Section: Brachypodium: a Genome On A Dietsupporting
confidence: 82%
“…At the other extreme, cultivated barley has seven solo LTRs for every fulllength BARE element and wild barley (Hordeum vulgare ssp. spontaneum) and some other Hordeum species even higher ratios (Soleimani et al 2006;Vicient et al 1999b). The ratios for Hordeum reflect a relatively high turnover rate at least for BARE through solo LTR formation, despite the overall abundance of retrotransposons in the barley genome.…”
Section: Genome Dynamics and Retrotransposon Gain And Lossmentioning
confidence: 95%
See 1 more Smart Citation
“…In plants, the first time real-time PCR method was successfully used by Soleimani et al (2006) for quantification of BARE1 in five cultivars of barley (Hordeum vulgare) and two accessions of its wild relative, Hordeum spontaneum. Examining the LTR and reverse transcriptase domains revealed significant differences in BARE1 copy number among cultivars, providing further evidence that BARE1 is active and has a major role in shaping the barley genome as a result of breeding and selection.…”
Section: Diversity Analysis With Retrotransposon Markersmentioning
confidence: 99%